An Analysis of the Implementation of the Pancasila Student Profile Strengthening Project in Elementary School - Helmelia Putri; Awaluddin Muin; Mujahidah (Journal of Primary Education Innovation and Research, 2025)
This study aims to describe the implementation of the Pancasila Student Profile Strengthening Project, or P5, at SD Negeri 19 Toro, Kecamatan Tanete Riattang Timur, Kabupaten Bone. This study used a descriptive qualitative approach. Data were collected through interviews, observation, and documentation. The informants included the principal, homeroom teachers of Grades I, II, IV, and V, and student representatives. The data were analyzed using data reduction, data presentation, and conclusion drawing. The results showed that the implementation of P5 at SD Negeri 19 Toro had been carried out but was not yet fully optimal. The implementation was analyzed through three main aspects: planning, implementation, and evaluation. In the planning stage, the school had determined project themes, arranged the schedule, formed a facilitator team, and prepared project modules. In the implementation stage, P5 was carried out using a thematic approach and a block system through activities such as gardening, waste recycling, and introducing traditional Bugis food. In the evaluation stage, teachers assessed students’ participation, cooperation, creativity, and project products through observation, reflection, presentation, and documentation. However, several obstacles were found, including the lack of special training for teachers, limited facilities and infrastructure, varied student readiness, and limited parental involvement. Therefore, the implementation of P5 at SD Negeri 19 Toro can be categorized as being in the developing stage. Further improvement is needed in teacher training, project planning, supporting facilities, and parental involvement so that P5 can be implemented more effectively and meaningfully for students.